1954
DOI: 10.1161/01.res.2.5.405
|View full text |Cite
|
Sign up to set email alerts
|

The Participation of the Venomotor System in Pressor Reflexes

Abstract: In dogs anesthetized with chloralose, innervated loops of intestine were isolated so as to permit periodic interruptions of blood flow to record pressure-volume diagrams from the venous bed. Pressor reflexes were found to produce alterations in the venous distensibility diagrams which, on the basis of comparison with distensibility changes produced by constrictor drugs, are interpreted as direct evidence of venoconstriction accompanying pressor responses of the cardiovascular system. I NVESTIGATIONS of the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

1957
1957
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 6 publications
0
36
1
1
Order By: Relevance
“…Heymans & Neil (1958) have stressed the contribution of venoconstriction to any rise in cardiac output. Though the degree of limb vein constriction when sinus pressure is reduced may be small (Browse, Donald & Shepherd, 1966;Bevegard & Shepherd, 1966;Brender & Webb-Peploe, 1969), venoconstriction in the splanchnic bed seems well-established (Alexander, 1954;Oberg, 1964;Brender & Webb-Peploe, 1969). Reports of structural alterations in the rabbit vasculature induced experimentally by steroids or as a result of pregnancy (Danforth, Manalo-Estrella & Buckingham, 1964), of increased venous distensibility produced in women by pregnancy or oestradiol (Goodrich & Wood, 1964, and of inhibition by oestradiol and progesterone of the response to electrical stimulation of strips of human venous smooth muscle (Barwin & McCalden, 1972), may indicate therefore that impaired venous contractility could contribute to the smaller responses which we have observed in the pregnant rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…Heymans & Neil (1958) have stressed the contribution of venoconstriction to any rise in cardiac output. Though the degree of limb vein constriction when sinus pressure is reduced may be small (Browse, Donald & Shepherd, 1966;Bevegard & Shepherd, 1966;Brender & Webb-Peploe, 1969), venoconstriction in the splanchnic bed seems well-established (Alexander, 1954;Oberg, 1964;Brender & Webb-Peploe, 1969). Reports of structural alterations in the rabbit vasculature induced experimentally by steroids or as a result of pregnancy (Danforth, Manalo-Estrella & Buckingham, 1964), of increased venous distensibility produced in women by pregnancy or oestradiol (Goodrich & Wood, 1964, and of inhibition by oestradiol and progesterone of the response to electrical stimulation of strips of human venous smooth muscle (Barwin & McCalden, 1972), may indicate therefore that impaired venous contractility could contribute to the smaller responses which we have observed in the pregnant rabbits.…”
Section: Resultsmentioning
confidence: 99%
“…One may speculate that during the "control" portion of this study and in experiments reported by others (2-4, 6, 7, 17), this expansion of blood volume increased intravascular pressure. The consequent stimulation of arterial (20) and systemic venous baroreceptors (21) could have resulted in a decrease in venous tone resulting in an increased capacity of the venous bed at any given transmural pressure (21)(22)(23)(24). This decrease in venous tone, in turn, could result in a tendency for the infused fluid to pool in the systemic venous bed, which would minimize any augmentation of the volume of blood in the heart and lungs (25).…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that as a consequence of the partial ganglionic blockade induced by Arfonad, venous tone diminished, the capacity of the venous bed increased and the central blood volume, cardiac output, and left ventricular work fell. However, it would appear likely from the observations of Alexander (22), that when venous tone diminishes, for any given increment in venous blood volume the transmural venous pressure rises to a greater extent than when the venous bed is initially partially constricted. This would permit a larger fraction of the infused blood to enter the thorax and cardiac output to rise significantly.…”
Section: Discussionmentioning
confidence: 99%
“…One mneans by which such regulation can be achieved is through l)arorecel)tor-mediated reflexes, and substantial evidence is available to sul)port the contention that this system plays an important role in the regulation of the degree of Nrenocoinstriction. Thus, a number of investigations hav-e (lemolnstrated that a reduction in carotid sinus pressure produces venoconstriction in the dog (7)(8)(9)(10)(11)(12), and that carotid sinus hypertension prodluces venodilation (7,9,10). As a result of such studies, in their moiiograph Heymans and Neil wrote that "the most important change (luring reflex systemic hypertension of sino-aortic origin is Jrobably that of venoconstriction" (13).…”
Section: Introductionmentioning
confidence: 99%
“…The role of the baroreceptor system in regulating venous tone in man is also disputed. Thus, upright tilt, lower-body negative pressure, and drug-in-(luced hypotension have all been shown to be followed by venoconstriction ( 1 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; on the other hand, several recent studies have shown that the venoconstriction after upright tilt and lowerbody negative pressure occurs irregularly and is generally slight and transient (21)(22)(23). It has been our experience in studies on conscious man that it is often extremely difficult to determine whether an increase in venous tone after an intervention which decreases baroreceptor activity is truly mediated by the baroreceptor system, or is the result of the well-known responsiveness of the venous system to many sensory and emotional stimuli.…”
Section: Introductionmentioning
confidence: 99%